Corrosion effect on the flexural behaviour of concrete filled steel tubulars with single and double skins using engineered cementitious composite. (October 2022) - Alraeeini, Ahmed Saleh; Nikbakht, Ehsan
Abstract: Concrete filled double skin tubular (CFDST) members are considered one of the most advanced construction composite forms, consisting of inner and outer tubes with concrete sandwiched between them. This paper presents an experimental study and theoretical analysis of the flexural performance of corroded concrete filled steel tubular (CFST), compared to CFDST beams with engineered cementitious composite (ECC) and normal concrete (NC). ECC is characterised by excellent tensile and flexural behaviour with crack control capacity, which shows great potential for enhancing the flexural behaviour of CFDST, especially in aggressive marine environments. In this study, a 500 µA/cm 2 current density was implemented for 170 and 250 h to produce accelerated corrosion with mass losses of 6 % and 9 %, respectively, to investigate the effect of corrosion on the flexural behaviour of regular CFDST and CFDST with different types of infill material. Moreover, due to the shortcomings of normal concrete in preventing both the outward and inward buckling of steel plates, in this study an ECC was incorporated as the infill material between steel tubulars. The experimental results of all samples, including CFST and CFDST, showed that corrosion affects the flexural stiffness, ductility index, and energy absorption more than the ultimate moment strength. In addition, the highest impact of corrosion was for CFST with NC (CFST-NC), whereas the lowest effect was observed in CFDST with ECC (CFDST-ECC). Moreover, there is a lack of consideration regarding the impact of corrosion on the predicted flexural stiffness provided by existing codes. Hence, in this study, a theoretical flexural stiffness analysis was conducted and compared with various codes such as EC4, AIJ, BS5400, and AISC.